2016
DOI: 10.1002/slct.201600152
|View full text |Cite
|
Sign up to set email alerts
|

Mn Ion substituted CeO2Nano spheres for Low Temperature CO Oxidation: The Promoting Effect of Mn Ions

Abstract: A series of Ce1‐xMnxO2‐δ (x=0.0, 0.1, 0.2, 0.3, 0.4, 0.5) nanocatalysts were prepared by solution combustion synthesis. XRD results confirmed the absence of bulk manganese oxide in Ce1‐xMnxO2‐δ indicating the substitution of Mn ion in ceria matrix. The percentage C and N doping in Ce1‐xMnxO2‐δ was quantified with a CHN analyzer, whereas, the mesoporous nature of the catalysts was confirmed by N2 physisorption analysis. Raman, H2‐TPR results confirmed the increasing oxygen vacancies on Mn substitution, whereas,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…Chen et al [28] synthesized Co 3 O 4 -CeO 2 core-shell catalysts and proved that the synergistic effect between Co 3 O 4 and CeO 2 is responsible for their enhanced catalytic activity compared with that of regular catalysts. Narayana et al [29] prepared spherical CeO 2 nanoparticles with Mn-ion substitution and observed the highest CO oxidation rate for the structure with the highest amounts of Mn 2+ as well as oxygen vacancies. Obviously, nanoscale catalysts exhibit excellent catalytic performances due to the size effect and their special morphology.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al [28] synthesized Co 3 O 4 -CeO 2 core-shell catalysts and proved that the synergistic effect between Co 3 O 4 and CeO 2 is responsible for their enhanced catalytic activity compared with that of regular catalysts. Narayana et al [29] prepared spherical CeO 2 nanoparticles with Mn-ion substitution and observed the highest CO oxidation rate for the structure with the highest amounts of Mn 2+ as well as oxygen vacancies. Obviously, nanoscale catalysts exhibit excellent catalytic performances due to the size effect and their special morphology.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the presence of Ag facilitates the stability of the gold supported catalysts . (iii) The CeO 2 shell, which is with excellent redox properties and oxygen storage capability, facilitates the CO oxidation process . Moreover, the efficiency of CeO 2 to provide oxygen is greatly raised in the presence of silver even at high temperatures, which further improve the catalytic activity of the SACs in CO oxidation …”
Section: Resultsmentioning
confidence: 99%
“…However, it is still possible that we have small Mn x O y islands on the ceria surface and they are active like Co 3 O 4 providing additional active sites. For manganese, this high doping level was previously proven to be effective for CO oxidation [50].…”
Section: Co Oxidation Activitymentioning
confidence: 97%